Assessment of business studies’ challenges on teaching-learning process for self-sustainability among graduates in Oyo State, Nigeria (2021)
This study examined business studies’ challenges on teaching-learning process among students in Nigerian educational system. This study made use of descriptive research design of survey type and the population of interest is the undergraduates and lecturers that are teaching and learning business studies. The sample is made up of 330 business studies undergraduates and business lecturers. Stratified random sampling technique was used to select the participants. Data were collected through the use of questionnaire tagged challenges of Business studies among business studies students and lecturers in Nigerian educational system with reliability coefficient of 0.79. Section A consists of socio-demographic information while Section B consists of checklists of challenges of Business studies among students and lecturers in Nigerian educational system. The findings of the study showed that students took business studies and lecturers taught amidst a lot of challenges such as inadequate teaching facilities, political interference, poor funding, lack of qualified teachers of business studies, failure to accept and adopt single curriculum across the nation, the use of outdated curriculum and finally the attitude of learners and society towards business studies as a course meant for average students that are not educationally vibrant. Based on these findings the researcher concluded that the teaching-learning process of business studies has a lot of challenges. Therefore, the following recommendations were made that students must see the study of business studies as equivalent to any other courses their colleagues are reading, government must fund the business studies just like any other courses like engineering, medicine, agricultural sciences. The experts must be employed to teach business studies. The facilities for teaching business studies must be made available to prevent examination malpractices and half baked graduate. Professional and highly skilled business studies teachers should be recruited to help improve the skills of the students in the various institutions where teaching-learning process in business studies is being running.